2022
DOI: 10.2991/assehr.k.220102.046
|View full text |Cite
|
Sign up to set email alerts
|

Law Enforcement of Criminal Acts of Terrorism Through a Humanist Approach based on Pancasila Law

Abstract: Pancasila, as the source of all sources of state law, is the result of deep exploration, analysis, and reflection by the founding national figures of the Republic of Indonesia. All aspects and values of civilization, history, geography, demography, religion, ethnicity, culture, customs are united in five basic values (grand norm), and each value which is one with other values is an inseparable unity. Terrorism and radicalism are real threats to the existence of Pancasila as an ideology. It takes consistency, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Based on the results of this research and discussion, it is suggested that the government and related parties improve compensation and restitution arrangements in criminal law by prioritizing the principles of justice and humanity found in Pancasila values (Widhiarto & Soerjatisnanta, 2022). In addition, collaboration and participation from all parties are also needed to ensure a more dignified arrangement for victims of criminal acts.…”
Section: Principles Of Dignified Justice Compensation and Restitution...mentioning
confidence: 98%
“…Based on the results of this research and discussion, it is suggested that the government and related parties improve compensation and restitution arrangements in criminal law by prioritizing the principles of justice and humanity found in Pancasila values (Widhiarto & Soerjatisnanta, 2022). In addition, collaboration and participation from all parties are also needed to ensure a more dignified arrangement for victims of criminal acts.…”
Section: Principles Of Dignified Justice Compensation and Restitution...mentioning
confidence: 98%